An integrative analysis of post-translational histone modifications in the marine diatom Phaeodactylum tricornutum - Veluchamy, Alaguraj; Rastogi, Achal; Lin, Xin; Lombard, Bérangère; Murik, Omer; Thomas, Yann; Dingli, Florent; Rivarola, Maximo Lisandro; Ott, Sandra; Liu, Xinyue; Sun, Yezhou; Rabinowicz, Pablo D.; et al. (BioMed Central, 2019)
Background: Nucleosomes are the building blocks of chromatin where gene regulation takes place. Chromatin landscapes have been profiled for several species, providing insights into the fundamental mechanisms of chromatin-mediated transcriptional regulation of gene expression. However, knowledge is missing for several major and deep-branching eukaryotic groups, such as the Stramenopiles, which include the diatoms. Diatoms are highly diverse and ubiquitous species of phytoplankton that play a key role in global biogeochemical cycles. Dissecting chromatin-mediated regulation of genes in diatoms will help understand the ecological success of these organisms in contemporary oceans. Results: Here, we use high resolution mass spectrometry to identify a full repertoire of post-translational modifications on histones of the marine diatom Phaeodactylum tricornutum, including eight novel modifications. We map five histone marks coupled with expression data and show that P. tricornutum displays both unique and broadly conserved chromatin features, reflecting the chimeric nature of its genome. Combinatorial analysis of histone marks and DNA methylation demonstrates the presence of an epigenetic code defining activating or repressive chromatin states. We further profile three specific histone marks under conditions of nitrate depletion and show that the histone code is dynamic and targets specific sets of genes. Conclusions: This study is the first genome-wide characterization of the histone code from a stramenopile and a marine phytoplankton. The work represents an important initial step for understanding the evolutionary history of chromatin and how epigenetic modifications affect gene expression in response to environmental cues in marine environments.